Differential Roles of Two Leptin Gene Paralogues on Food Intake and Hepatic Metabolism Regulation in Mandarin Fish - Yuan, Xiao-Chen; Liang, Xu-Fang; Cai, Wen-Jing; Li, Ai-Xuan; Huang, Dong; He, Shan (Frontiers in Endocrinology, 2020)
Leptin affects food intake regulation and energy homeostasis in mammals. As opposed to mammals who have a single leptin gene, fish have duplicated leptin gene paralogues. Until now, almost functional studies on fish focused on the first reported paralogue without much explanation on specific gene paralogue. This study successfully expressed two homologous recombinant mandarin fish leptin genes (LepA and LepB) for the first time. To explore the differential roles of these two gene paralogues involved in food intake and energy homeostasis, mandarin fish were treated with homologous recombinant LepA and LepB proteins by acute IP administration. The results showed that LepB inhibited the food intake of mandarin fish after acute IP administration through modifying the expressions of hypothalamic orexigenic genes, while LepA had no significant effect on its food intake. In addition, LepB administration decreased the hepatic glycogen level through regulating the gene expressions of glycogen synthase and glycogen phosphorylase in mandarin fish until 4 d, while LepA did not change the hepatic glycogen level as it failed to change the expressions of these regulatory genes. Moreover, LepA and LepB downregulated the expressions of key gluconeogenic genes (phosphofructokinase, phosphoenolpyruvate carboxykinase and glucose-6-phosphatase), indicating both mandarin fish leptins could regulate the rate of glucose production. However, these two gene paralogues presented secondary effects on lipid metabolism as they only enhanced the triglyceride level by modifying the gene expressions of adipose triglyceride lipase or acetyl CoA carboxylase just for 1 d after IP. Therefore, LepB played an important role in food intake and glucose homeostasis regulation, while LepA showed a limited role in gluconeogenesis and lipid metabolism.